Knowledge and management of chronic spontaneous urticaria in Latin America: a cross-sectional study in Ecuador - Cherrez, Annia (World Allergy Organization journal, 2017)
The current EAACI/GA2LEN/EDF/WAO guideline for urticaria provide specific recommendations for the diagnostic workup and treatment of patients with chronic spontaneous urticaria (CsU). This study explored if physicians in Ecuador know these recommendations and implement them in their actual clinical practice for CsU.